THE INTERNSHIP PROGRAM BRIDGES THE COMPETENCY GAP BETWEEN AGRICULTURAL VOCATIONAL EDUCATION GRADUATES AND INDUSTRY WORK READINESS STANDARDS - Dwi Haryanta; Endrayana Putut Laksminto Emanuel (Universitas Tribhuwana Tunggadewi, 2025)
This study examines initiatives to close the gap between graduates of agricultural vocational education's academic proficiency and their preparedness for the workforce based on graduate users' standards, specifically those of the industrial sector. This study looks at the competency accomplishments of graduates in agriculture education during the fourth industrial revolution, a time when the global labor market is competitive and full of obstacles. We start this conversation by gathering information from foreign periodicals and literature sources. A qualitative narrative analysis that incorporates a coding system, critical review, and a conclusion that satisfies the findings' validity and reliability principles. Google Docs, Google Scholar, and Eric journals with a range of publications from 2015 to 2025 were used. We looked at evaluation methods and learning tactics and procedures, discovered that the majority of studies on the academic proficiency of graduates of agricultural vocational education fall short in terms of practical field competences, which are necessary to achieve industry and business work-readiness norms, promote cooperation between agricultural vocational education institutions and the agricultural industry/business world, which employs graduates, proposes methods and solutions. Most publications promote the inclusion of the skills and work competencies required of graduates in the curriculum as a guide for designing learning outcomes, learning models, and methodologies. Students can put their practical knowledge and skills to the agricultural sector, businesses and academic institutions collaborate to plan, implement, and evaluate partnerships. The results will greatly enhance the cooperation between agricultural educational establishments and the commercial and industrial sectors that hire agricultural graduates.